Prognostic impact of Clinical Frailty Scale in patients with heart failure with preserved ejection fraction. (20th June 2021) - Sunaga, Akihiro; Hikoso, Shungo; Yamada, Takahisa; Yasumura, Yoshio; Uematsu, Masaaki; Tamaki, Shunsuke; Abe, Haruhiko; Nakagawa, Yusuke; Higuchi, Yoshiharu; Fuji, Hisakazu; Mano, Toshiaki; Kurakami, Hiroyuki; et al.
Abstract: Aims: Frailty is associated with prognosis of cardiovascular diseases. However, the significance of frailty in patients with heart failure with preserved ejection fraction (HFpEF) remains to be elucidated. The purpose of this study was to examine the prognostic significance of the Clinical Frailty Scale (CFS) in real‐world patients with HFpEF using data from a prospective multicentre observational study of patients with HFpEF (PURSUIT‐HFpEF study). Method and Results: We classified 842 patients with HFpEF enrolled in the PURSUIT‐HFpEF study into two groups using CFS. The registry enrolled patients hospitalized with a diagnosis of decompensated heart failure. Median age was 82 [interquartile range: 77, 87], and 45% of the patients were male. Of 842 patients, 406 were classified as high CFS (CFS ≥ 4, 48%) and 436 as low CFS (CFS ≤ 3, 52%). The primary endpoint was the composite of all‐cause mortality and heart failure admission. Secondary endpoints were all‐cause mortality and heart failure admission. Patients with high CFS were older (85 vs. 79 years, P < 0.001), predominantly female (65% vs. 46%, P < 0.001) and more likely to have New York Heart Association (NYHA) ≥ 2 (75% vs. 53%, P < 0.001) and a higher level of NT‐proBNP (1360 vs 838 pg/mL, P < 0.001) than those with low CFS. Patients with high CFS had a significantly greater risk of composite endpoint (Kaplan–Meier estimated 1‐year event rate 39% vs. 23%, log‐rank P < 0.001), all‐cause mortality (Kaplan–Meier estimated 1‐year event rate 17% vs. 7%, log‐rank P < 0.001) and heart failure admission (Kaplan–Meier estimated 1‐year event rate 28% vs. 19%, log‐rank P = 0.002) than those with low CFS. Multivariable Cox regression analysis revealed that high CFS was significantly associated with composite endpoint (adjusted HR 1.92, 95% CI 1.35–2.73, P < 0.001), all‐cause mortality (adjusted HR 2.54, 95% CI 1.39–4.66, P = 0.003) and heart failure admission (adjusted HR 1.55, 95% CI 1.03–2.32, P = 0.035) even after adjustment for covariates. Moreover, change in CFS grade was also significantly associated with composite endpoint (adjusted HR 1.23, 95% CI 1.11–1.36, P < 0.001), all‐cause mortality (adjusted HR 1.32, 95% CI 1.13–1.55, P = 0.001) and heart failure admission (adjusted HR 1.15, 95% CI 1.02–1.30, P = 0.021). Conclusions: Frailty assessed by the CFS was associated with poor prognosis in patients with HFpEF.